The Readiness for Implementation of Financial Management Patterns of Regional Public Services Agency at Public Health Center - Evada Dewata; Hadi Jauhari (JASF: Journal of Accounting and Strategic Finance, 2021)
The purpose of the study is to determine the readiness of Lais public health center and Teluk Kijing public health center of Musi Banyuasin District, South Sumatra Indonesia, in managing finances of regional public service agencies (BLUD). Time of research from March-July 2021. Used the types of descriptive qualitative research to review the documents, observation, and in-depth interviews to the research subject as many as 10 (ten) informants. The triangulation technique is used in testing the validity of the data. The research result showed that Lais public health center and Teluk Kijing public health center were ready to implement the financial management pattern of BLUD, which can be seen from the results of input analysis, process, and output from the analysis of stakeholder, related commitment, knowledge and responsibilities, funding (money), infrastructure (materials) and methods, in addition, substantive requirements, technical requirements, and administrative requirements have been carried out. The results of this study have implications related to the preparation and continuation of the implementation of the BLUD Public Health Center financial management pattern. Based on its limitation, it is still possible for other local governments who have the same contextual conditions to use these results as an input when preparing the BLUDs financial management pattern.